Case Report: Free fibula flap for post-oncologic mandibular reconstruction, first experience in Tirana - Marzi Manfroni, Alice; Sako, Marjon; Mataj, Nela; Zhupa, Deniada; Laganà, Francesco (Frontiers in Oncology, 2025)
Mandibular reconstruction using an osteocutaneous free fibular flap is a highly advanced microsurgical procedure, rarely performed in developing healthcare systems due to technical complexity and infrastructure demands. We present the first successful case performed in Tirana, Albania, demonstrating the feasibility of implementing such techniques in emerging surgical settings. A 54-year-old male diagnosed with squamous cell carcinoma of the left mandibular alveolar crest (cT4N1M0) underwent left hemimandibulectomy, bilateral neck dissection and immediate mandibular reconstruction using a right osteocutaneous fibular free flap. Preoperative Doppler ultrasonography confirmed sufficient vascular supply, excluding contraindications such as peripheral vascular disease and venous insufficiency. Fibula was harvested without tourniquet, improving vascular visualization and reducing ischemic time. A 4 × 7 cm skin paddle was included for intraoral soft tissue reconstruction. Cervical recipient vessels were isolated for microvascular anastomosis. Postoperative management involved intensive monitoring by a multidisciplinary team. Flap viability was assessed through color, temperature, capillary refill, and Doppler signals, with early mobilization and speech/swallowing therapy initiated promptly. The patient experienced an uneventful recovery with complete flap survival and functional restoration. This case highlights the potential to achieve complex microvascular reconstructions successfully in resource-limited environments through careful planning and interdisciplinary collaboration.